How to develop an inclusive strategy to strive the social stratification of female entrepreneurs - Herlina, Fristi; Hidayat, Kliwon; Kustanti, Asihing (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2024)
Social stratification affects certain aspects of life, including gender equality in entrepreneurship. This study aims to analyze social stratification between women entrepreneurs who are members of the Melati Women’s Cooperative and non-members in Campurejo Village, Bojonegoro Sub-district, and their impact on their entrepreneurial output. This research uses a quantitative approach with descriptive comparative tests and linear regression analysis. Data were collected through questionnaires from 140 female entrepreneurs. The results show that the social stratification of cooperative member women entrepreneurs, characterized by socioeconomic status, education, wealth, honor, and social interaction, significantly differs from that of the non-member. Cooperative members have better access to resources, business networks, and economic opportunities than non-members. They experience strong solidarity and support among members, helping them overcome business challenges. Non-members face isolation and difficulties competing in the market due to limited access to capital and business networks. This study confirms that cooperative membership can reduce social stratification and enhance women entrepreneurs’ economic empowerment. This study also revealed that social stratification significantly influences entrepreneurial output, with cooperative members showing better business outcomes. These findings are crucial for developing policies that support cooperatives as a mechanism of social mobility for female entrepreneurs with the aim of creating a more inclusive and equitable society.JEL Classification D10; P13; Q13